KONSEP MANAJEMEN PENDIDIKAN KARAKTER DALAM MEMBENTUK AKHLAKUL KARIMAH DI MTs MA’ARIF NU KEMIRI - Farida, Ida; Kamalia , Aslimatun Ana (Managere: Indonesian Journal of Educational Management, 2020)
This paper discusses the concept of management of character education in MTs Ma'arif NU Kemiri, the concept in question is the pattern of character formation of students with various supporting elements such as madrasa activities, rules or regulations, and content of Islamic education lessons that are applied in MTs Ma'arif NU Kemiri. In addition to these supporting elements, in order to shape the character of morality also has several strategies in supporting the achievement of character education management concepts such as: exemplary, learning, empowerment and acculturation, retention, and assessment.